Screening OSA in Chinese Smart Device Consumers: A Real-World Arrhythmia-Related Study - Chen Y; Zhang H; Li J; Xu P; Guo Y; Xie L (Nature and Science of Sleep)
Yibing Chen,1 Hui Zhang,2 Jing Li,3 Peida Xu,3 Yutao Guo,2 Lixin Xie4,5 1Department of Pulmonary and Critical Care Medicine, The First Medical Center of Chinese PLA General Hospital, Beijing, 100853, People’s Republic of China; 2Department of Pulmonary Vessel and Thromboembolic Disease, The Sixth Medical Center of PLA General Hospital, Beijing, 100142, People’s Republic of China; 3HUAWEI Device Co., Ltd., Shenzhen, 518129, People’s Republic of China; 4College of Pulmonary and Critical Care Medicine, The Eighth Medical Center of Chinese PLA General Hospital, Beijing, 100091, People’s Republic of China; 5Chinese Association of Geriatric Research, Beijing, 100853, People’s Republic of ChinaCorrespondence: Lixin Xie, Email xielx301@126.comIntroduction: Early detection of obstructive sleep apnea (OSA) is critical due to its link to cardiovascular diseases. Our previous study validated an algorithm-based photoplethysmography (PPG) smartwatch for OSA risk detection.Objective: This study aimed to characterize OSA features and assess its association with arrhythmia risk among smart wearable device (SWD) consumers in China in a real-world setting.Methods: Between December 15, 2019, and January 31, 2022, SWD consumers across China were screened for OSA risk using HUAWEI devices. OSA diagnosis was confirmed via telecare follow-ups, including clinical evaluations and sleep test records. Disease characteristics and arrhythmia risks were analyzed.Results: In a large cohort of 1,056,494 participants, smart wearable devices (SWDs) effectively identified 19,563 individuals at high risk for OSA, with 1054 confirmed cases. OSA patients demonstrated high prevalence of obesity (46.8%), hypertension (19.8%), and arrhythmia (17.17%). SWDs detected abnormal heart rhythms or suspected arrhythmia in 95.9% of confirmed OSA cases. Age emerged as an independent predictor of arrhythmia risk, while hypertensive OSA patients were older, more obese, and experienced prolonged nocturnal hypoxia (Time length of SpO2< 90%, P=0.020). These findings underscore the utility of SWDs in OSA screening and highlight the significant cardiovascular risks associated with OSA.Conclusion: PPG-based SWD effectively screened for OSA and identified elevated arrhythmia risks. These findings support their utility for large-scale OSA screening and highlight cardiovascular risks management.Clinical Trial Registry Name: Mobile Health (mHealth) technology for improved screening, patient involvement and optimizing integrated care in atrial fibrillation.Registration Number: ChiCTR-OOC-17014138.Date of Registration: 2017– 12-26.Date of Last Refreshed On: 2018– 11-18.Keywords: obstructive sleep apnea, smart wearable device, arrhythmias, hypertension